A comparative analysis of critical power models in elite road cyclists - Clark, B.; Macdermid, P. W. (Current Research in Physiology, 2021)
The aims of this study were to compare four different critical power model's ability to ascertain critical power and W' in elite road cyclists, while making comparison to power output at respiratory compensation point, work rate (J/sec) at Wmax, and the work done above critical power during the Wmax test in relation to the W`. Ten male, elite endurance cyclists (VO2max = 71.9 ± 5.9 ml/kg/min) all familiar with critical power testing, participated in 3 testing sessions comprising 1. 15-s isokinetic (130 rpm) sprint, 1-min time trial, a ramp test to exhaustion, 2-3. a 4-min and/or 10-min self-paced maximal time trial separated by at least 24-h but limited to a 3-week period. The main findings show that all critical power models provided different W` (F(1.061,8.486) = 39.07, p = 0.0002) and critical powers (F(1.022,8.179) = 32.31, p = 0.0004), while there was no difference between each model's critical power and power output at respiratory compensation point (F(1.155, 9.243) = 2.72, p = 0.131). Differences between models or comparisons with respiratory compensation point were deemed not clinically useful in the provision of training prescription or performance monitoring if the aim is to equal work rate at compensation point. There was also no post-hoc difference between work completed at Wmax (kJ) (p = 0.890) and W' using the nonlinear-3 model. Further research is required to investigate the physiological markers of intensity associated with respiratory compensation point and critical power work rate and the bioenergetic contribution to W`.